Protein and Omega-3 Polyunsaturated Fatty Acid Supplementation for 16 Weeks Improves Sleep and Mood States in Postmenopausal Women. (29th May 2020) - Baum, Jamie; Hawley, Aubree; Baughn, Caroline; Walker, Sam; Tacinelli, Angela; Gray, Michelle
Abstract: Objectives: Body composition shifts as we age, resulting in loss of skeletal muscle mass with an increase in fat mass, which is linked to disruptions in sleep-wake rhythms and mood disturbance. Current evidence suggests protein and omega-3 polyunsaturated fatty acids (O3FA) individually augment sleep quality and attenuate depression, but a concomitant effect is yet to be determined. The objective of this study was to determine the effect of protein and O3FA supplementation on regulation of sleep and mood states in postmenopausal women. Methods: Overweight, postmenopausal women (60.6 ± 9.0 years; BMI: 28.1 ± 6.9) participated in this randomized, controlled, single-blinded, 16 wk dietary intervention. Participants were allocated to 1 of 5 groups: 1) control, no INT ( n = 6); 2) whey protein isolate (PRO; 25 g/d; n = 4); 3) O3FA (DHA/EPA; 4.3 g/d; n = 10); 4) PRO + soy bean oil (4.3 g/d) placebo ( n = 6), and 5) PRO + O3FA ( n = 8). Sleep (via Pittsburgh Sleep Quality Index Global Sleeping Score; PSQI GSS) and total mood disturbances; (TMD; via Profile of Mood States (POMS)) including six affect states of depression, fatigue, anger, tension, confusion, and vigor subscales were assessed at 0, 4, 8, 12, and 16 wks. Sleep was measured at 0, 8, and 16 wk via wrist Actigraphy. Body composition was measured via DXA at 0 and 16 wk. Data were analyzed using two-way ANOVA to assess the relationship between diet, sleep, and mood states over time. Results: Overall, all interventions improved PSQI GSS ( P < 0.05) by 16 wks. There was a trend for all interventions to improve sleep efficiency ( P = 0.06), with no effect on total sleep time. All interventions improved TMD ( P < 0.05) and vigor ( P < 0.001), with a trend on depression ( P = 0.06). PRO, O3FA, and O3FA + PRO significantly improved vigor at 12-wks ( P < 0.01). PRO alone significantly improved vigor at 16 wk ( P < 0.001) compared to CON. There was no significant effect of intervention on body composition. However, PRO, O3FA, and PRO + O3FA had a positive (564.7 ± 681.4 g) and the CON had a negative (−171.0 ± 991.6) net change of total lean mass at 16 wks. Conclusions: This pilot study suggests that PRO, O3FA, and PRO + O3FA have potential to improve sleep and mood in overweight, postmenopausal women. Additional research is needed to determine the long-term individual and concomitant effect of PRO and O3FA on sleep and mood states. NCT0303041. Funding Sources: Arkansas Biosciences Institute.